EVALUASI PENGENDALIAN KUALITAS AIR MINUM PADA DEPOT AIR MINUM ISI ULANG DI KABUPATEN SLEMAN, YOGYAKARTA - Baziedy Aditya Darmawan (Universitas Islam Indonesia, 2016)
Water situation is problematic to make people choose to consume bottled drinking water. However, the more expensive bottled drinking water on the market. making people switch to consume water from a much cheaper DAMIU. Al though less expensive, not all products DAMIU security guaranteed. Some of the findings mentioned that DAMIU in some major cities do not fit the standards specified in Permenkes Number907/Menkes/SKA/II/2002. The problem in this study is, whether there are deviations in product quality DAMIU in Sleman district, and what factors influence it. The method used is the method of Statistical Quality Control and Ishikawa Diagram. This finding states that there are irregularities which do not fit the quality standards of the content of E-coli, pH, and Fe.Key words: Control, Quality, Depot, Water, Drinking